Graph drawing and network visualization : 23rd international symposium, GD 2015, Los Angeles, CA, USA, September 24-26, 2015 : revised selected papers /: 23rd international symposium, GD 2015, Los Angeles, CA, USA, September 24-26, 2015 : revised selected papers. (2015) - Unknown
No abstract available